Proposta e implementação de um plano de qualidade para obras públicas de pequeno porte - Carmen Pedrosa Perez (2011)
This study aimed to develop a set of procedures and standards related to the school buildings reform and expansion work managed by associations called Caixa Escolar, constitute a Quality Plan in Enterprises (QPE) for small-scale projects and analyze the results of implementing this Plan within the Minas Gerais State Department ofEducation. The study is characterized as an action research characterized by an exploratory diagnosis based on literature review and an intervention guided by the public administration principles (morality, impartiality, efficiency, transparency, legality). Minas Gerais State makes use of bidding mechanisms for contracting and executing its works, which are protected by Law 8.666/1993, State Decree 45.085/2009 and Resolution 1.346/2009. Thus, the QPE developed involves many internal bureaucratic procedures and is distinct from any private companies quality plan. It aims to meet the short duration and low income projects specificities and characteristics, in most cases performed by small businesses. It is subdivided into four modules: Design Quality Plan, Review of Contract, Quality and Inspection of Work. In order to verify their viability, the proposal was implemented in three reform school buildings works with different results, as well as different difficulties levels due to some resistance encountered. Overall, it was observed that the inclusion of technical and managerial requirements supposes an advance in the works management with some improvement of quality, reducing environmental impact and working conditions and safety improvement on construction sites. One concludes that the QPE was submitted properly grounded and may possibly evolve further by inserting new control and management capabilities, using new tools for its continuous improvement. Somehow, the QPE breaks with archaic and even unethical practices existing in small and short public works. Furthermore, responding to the study questioning, the QPE presents itself as an efficient alternative mechanism in order to the government reaches mechanisms for continuous buildings quality improvement through retrofitting works. One emphasizes its possible to implement quality plans in public enterprises complying with the legislation, since such plans impact the works quality, make all parties involved to engage in compliance with each step, the works are not delayed and significant rework are not generated. Consequently, the outcome is appropriate as per the executive project and several benefits are obtained. Its structure is sufficiently generic so that it can be implemented in another natures small-scale works, and in this sense future work will examine itseffectiveness in other public works management, contributing to improve quality and the increased buying power of public organisms.